Neighborhood effects and individual unemployment - Thomas K. Bauer; Michael Fertig; Matthias Vorell (Institute for the Study of Labor (IZA), 2011)
Using a unique dataset for Germany that links individual longitudinal data from the GSOEP to regional data from the federal employment agency and data of real estate prices, we evaluate the impact of neighborhood unemployment on individual employment prospects. The panel setup and richness of the data allows us to overcome some of the identification problems which are present in this strand of literature. The empirical results indicate that there is a significant negative impact of neighborhood unemployment on the individual employment probability.
urn:nbn:de:101:1-201110263842
Keywords: J64; R23; 330; social interactions; unemployment; neighborhood characteristics; Arbeitslosigkeit; Soziale Beziehungen; Nachbarschaft; Regionale Arbeitslosigkeit; Deutschland